Anticancer effects of disulfiram in T-cell malignancies through NPL4-mediated ubiquitin–proteasome pathway. Issue 4 (1st April 2022) - Chen, Cunte; Nie, Dingrui; Huang, Youxue; Yu, Xibao; Chen, Zheng; Zhong, Mengjun; Liu, Xin; Wang, Xianfeng; Sui, Songnan; Liu, Zhuandi; Tan, Jiaxiong; Yu, Zhi; et al.
Abstract: T-cell malignancies, including T-cell acute lymphoblastic leukemia (T-ALL) and T-cell lymphoma (TCL), are characterized by inferior treatment effects, high heterogeneity, poor prognosis, and a lack of specific therapeutic targets and drugs to improve outcome. Disulfiram (DSF) is a drug used to clinically control alcoholism that has recently been shown to be cytotoxic for multiple cancers. However, the underlying effects and mechanisms of DFS treatment in patients with T-cell malignancies are not well characterized. In this study, we report that DSF promotes apoptosis and inhibits the proliferation of malignant T-cell cell lines and primary T-ALL cells. We provide evidence that DSF exerts anticancer activity in T-cell malignancies by targeting the NPL4 -mediated ubiquitin–proteasome pathway. Notably, high expression of NPL4 and 2 ubiquitin–proteasome pathway genes, anaphase-promoting complex subunit 1 ( ANAPC1 ) and proteasome 26S subunit ubiquitin receptor, non-ATPase 2 ( PSMD2 ), was significantly associated with unfavorable overall survival (OS) for patients with TCL and T-ALL ( p  < 0.05). More importantly, the weighted combination of NPL4, ANAPC1, and PSMD2 could visually display the 1-, 3-, and 5-year OS rates for patients with T-cell malignancies in a nomogram model and facilitate risk stratification. Specifically, risk stratification was an independent predictor of OS for patients with T-cell malignancies. In conclusion, DSF might induce apoptosis and inhibit the proliferation of malignant T-cells via the NPL4-mediated ubiquitin–proteasome pathway and offer a potential therapeutic option for T-cell malignancies. Graphical Abstract: Disulfiram eradicates T-cell malignancies by targeting the NPL4-mediated ubiquitin-proteasome pathway, and NPL4, ANAPC1, and PSMD2 might be potential biomarkers for risk stratification.